Operational barriers in providing comprehensive emergency obstetric care by task shifting of medical officers in selected states of India - Vikash Ranjan Keshri; Bishan Swarup Garg (Wolters Kluwer Medknow Publications, 2021)
Background: A network of first referral unit (FRU) is set up to improve the availability and accessibility of comprehensive emergency obstetric care (CEmOC) services. To fill the gap of the scarcity of obstetricians and anesthetists at FRU, two short-term trainings in CEmOC and anesthesia were started for in-service medical officers. Objective: This study aimed to assess the operational status of FRU in providing CEmOC services by task shifting of trained medical officers in selected states of India. Materials and Methods: The study was done in seven states of India. A team of experts assessed conveniently selected health facilities designated as FRU by using a semi-structured, predesigned, and pretested checklist for CEmOC functionality status. A total of 50 designated FRUs were assessed and data were systematically analyzed. Results: We documented the availability of five key elements for the operationalization of CEmOC services at FRU. Out of 50 facilities, 9 (18%) reported conducting operative delivery and 11 (22%) of the facilities were fully operational with all elements available. At 9 (18%) facilities, one element and, at 17 (34%) facilities, two elements were missing. The blood storage unit was the most important missing element (68%) followed by operative facilities (36%). The challenges of FRUs remained uniform across states. Barriers identified to operationalize FRU were the availability of trained doctors in cesarean section and anesthesia together, lack of operative facilities, and blood storage units. Conclusions: To operationalize the network of FRU for CEmOC services by task shifting of medical officer, it is important to ensure the availability of all five key elements together at all facilities.